(untitled) (Global Journal of Science Frontier Research, 2015)
Kaluza Klein cosmological models with varying G in Hoyle Narlikar creation field theory of gravitation for barotropic fluid distribution have been investigated. The solution of the field equations have been obtained by assuming that G=A l , where A is a scale factor and l is a constant. The physical properties of the model are studied.